A HISTORY OF VIOLENCE: PERU BETWEEN THE YEARS 1980 TO 1997 - Cayuela Berruezo, Miguel (2020)
The Peruvian population it was the victim during the confrontation between armed forces and the terrorists in the decades of 1980 and 1990. This study is based on optics of historical memory. The article focuses mainly on the confrontation between the Armed Forces and Sendero Luminoso. During the fight, both slides forgot human rights, all for fulfilling their objectives, the main loser was Perú and its entire population. Perú between 1980 and 1997 experienced an era of uncontrolled violence, which marked the Peruvian nation forever.